Financing transportation networks - Levinson, David M. (Transport economics, management, and policy, 2002)
An approach that creates the local winners necessary to implement road pricing is required before it can be expected to become widespread." "Economists, civil engineers, planners, students and policymakers will find this detailed examination of transportation networks enlightening and useful."--BOOK JACKET